THE EFFICACY OF FORK TYPE HOE AND SINGLE BLADE HOE FOR HOEING WET RICE FIELD LAND IN POH MANIS VILLAGE, DENPASAR MUNICIPALITY - N, Adiputra; DP, Sutjana (Medicina; Vol 40 No 1 (2009): Januari 2009, 2014)
Balinese farmer in doing their daily activities in agricultural work still relay on their hand tools. One of the hand tools used is the hoe. In fact there are two type of hoe, fork type and single blade hoe.  The single blade hoe is very rare used for hoeing in wet rice field. Farmer chose the fork type one. Therefore, a study was conducted to compare the efficacy of those two hoes. Twenty farmers were participated voluntarily. They were divided into two groups evenly. The first group hoeing using the fork type hoe, and the second group using the single blade one. They hoeing in the same area of rice field (wet rice field) from 07.00 until 12.00. The parameter measured were resting and working heart rate, product and productivity, musculoskeletal disorders, and the deep of soil hoed. The student-t test was applied to analyses the results. The results found are: a) the working heart rate, the product and productivities were 111.1 ± 14.66 bpm; 127.74 ± 9.15 m2; 0.54 ± 0.00 and 110.2 ± 13.88 bpm; 126.88 ± 8.79 m2; 0.54 ± 0.00  for first group and second group, respectively. The MSD and the deep of soil hoed were 4.50 ± 1.97; 30.0 ± 2.54 cm and  4.45 ± 2.03; 29.64 ± 1.75 cm for both groups. There are no significant different found statistically. Therefore, it is concluded that the efficacy of single blade hoe is similar to the fork type hoe for hoeing the wet rice field in the tropic. For further study it is recommended to use these two hoes for hoeing in the dry soil.[ MEDICINA 2009;40:43-6 ].
Keywords: fork type, single blade hoe, product, productivity, Balinese farmer